Plasma FGF2 and YAP1 as novel biomarkers for MCI in the elderly: analysis via bioinformatics and clinical study - Zhao, Yejing; Wang, Xiang; Zhang, Jie; Zhao, Yanyan; Li, Yi; Shen, Ji; Yuan, Ying; Li, Jing (Frontiers in Neuroscience, 2025)
The contemporary consensus firmly emphasizes the urgent need to reorient research efforts toward the early detection of preclinical Alzheimer’s disease (AD) or mild cognitive impairment (MCI). However, there is still a notable absence of novel biomarkers that are both efficient, minimally invasive, and cost-effective in real-world clinical settings. To address this gap, datasets GSE29378 and GSE12685 were selected to screen differentially expressed genes (DEGs), and hub genes were identified by different algorithms. A total of 350 DEGs were identified in bioinformatics data mining. Functional enrichment analysis showed that fibroblast growth factor 2(FGF2) and yes-associated protein 1(YAP1) protein levels were highly expressed in AD samples, indicating their potential regulatory roles in AD. Between October and November 2024, a total of 146 elderly individuals diagnosed with MCI and 54 healthy elderly subjects were successfully recruited. Enzyme linked immunosorbent assay (ELISA) was used to detect plasma hub gene protein concentration. The results showed that the expression levels of plasma FGF2 and YAP1 proteins in the MCI group were significantly higher compared to the control group. Logistic regression analysis indicated that high plasma FGF2 and YAP1 expression levels were independently associated with MCI in the elderly. The Area under the curve (AUC) of FGF2 model and YAP1 model were 0.907 and 0.972, respectively. Therefore, the high expression of plasma FGF2 and YAP1 proteins may be independent predictive risk factors for MCI in the elderly. Our findings may provide targets for the development of early minimally invasive, efficient, and convenient screening tools, and even for the treatment of AD in the future.